Financial inclusion in India: an application of TOPSIS. Issue 3 (8th August 2016) - Yadav, Priyanka; Sharma, Anil Kumar
Abstract : Purpose: The purpose of this paper is to combine the critical parameters used to study financial inclusion into a composite index. The idea is to rank Indian states and union territories (UTs) on the basis of this index, determine change in ranks during 2011 to 2014 and identify factors affecting high/low scores on the index. Design/methodology/approach: Data for the study were collected from secondary sources published by Reserve Bank of India (RBI) and Central Statistical Organization. Applying technique of order preference by similarity to ideal solution (TOPSIS), a composite multi-dimensional index of financial inclusion (IFI) has been built by using three broad parameters of penetration, availability and usage of banking services. Factors significantly influencing scores of states/UTs on IFI were identified using multiple regression analysis. Findings: The value of financial inclusion for India on composite IFI has increased by 0.045 points during the study period. Share of agriculture to state gross domestic product, literacy ratio, population density, infrastructure development and farmer suicides are significant factors affecting financial inclusion. Practical implications: The multi-dimensional IFI is a useful tool to measure financial inclusion using several parameters for various states/regions. The index can also be used to compare the performance of states/regions over same/different periods. Originality/value: This paper is unique in its attempt to construct multi-dimensional IFI for Indian states/UTs by applying TOPSIS. It will prove useful for future researchers by combining several aspects of financial inclusion into single index.